The Importance of German Language Skills in the Tourism Sector - Herlina Jasa Putri Harahap (Britain International for Academic Research (BIAR) Publisher, 2020)
German plays an important role in the development of the tourism industry in Indonesia. This development must be in line with the competence and skills of the people who are involved in this industry, especially German language skills. In North Sumatera, there are various types of tour guides who have the potential to develop German language. A good understanding of German can increase the interest and comfort of German-speaking tourists visiting. Increase the competence of tour guides in German language and knowledge of German culture so that they can become professional tour guides who can promote tourist objects in North Sumatra to foreign tourists which have an impact on increasing regional income and reducing the unemployment rate. Education and training is needed to improve the German language skills of tour guides in North Sumatra, the best way is to provide education about tourism terms and dialogues in German and train the tour guides to be able to speak German both verbally and in writing with correct and correct according to the common european framework of reference for languages. Learning German for a guide requires several things to support the language learning process. Some of them are motivational factors, student learning strategies, and also the role of language instructors playing an important role in the success of tour guides in learning. There are factors related to learning German for tour guides and this is related to them as learners and direct actors in the learning process is motivation.